Making Sense of Barkhuizen 2 : An Investigation into the Public Policy Defence of 'Unfair Enforcement' in South African Law, with Reference to the Law on Covenants in Restraint of Trade - Moroeng, Tsukudu Kenyatta (Rhodes University, Faculty of Law, Law)
This thesis investigates the application of the public policy test for determining the enforceability of a valid contractual clause established in Barkhuizen v Napier. After analysing the historical development of the application of the doctrine of public policy, the study examines the conceptualisation and application of the public policy test in the leading cases in South Africa. The study then provides an analysis of the recent judgment of Beadica 231 CC and Others v Trustees for the time being of the Oregon Trust and Others, which outlined the current legal position on the proper constitutional approach to the judicial enforcement of valid contractual clauses. The study argues that, although the Constitutional Court in Beadica provided some clarity on what public policy is in modern South African law, it did not, from a practical point of view, set out the method that should be used to adjudicate such cases. The study thereafter suggests that, to address this issue, our courts should consider developing a methodological approach to measuring public policy in unfair enforcement cases. To support this proposition, the study examines the law on determining the enforcement of restraint of trade agreements. It is argued that, within that context, the courts have formulated a methodological approach in the form of a list of standard questions that a judge should ask when determining the enforceability of a restraint clause. The thesis then closes with a case study, using guidelines established from the approach in restraint cases, to illustrate how the proposed guideline may be formulated, and how it could be applied in general unfair enforcement cases. The thesis argues that a practical guide of this nature would serve as a useful tool for judges to use when faced with a claim relating to the unfair enforcement of a valid clause other than a restraint clause, and would thus ensure consistency in contractual enforcement analysis in South Africa.
Keywords: Restraint of trade -- South Africa; Public policy (Law) -- South Africa; Contracts (Roman-Dutch law); Customary law -- South Africa; Barkhuizen v Napier